Nat Turner and the Southhampton revolt of 1831 - Goldman, Martin S. (New York : F. Watts, 1992)
Describes the life of the slave and preacher who led the most successful slave rebellion in American history.
Spine title: Nat Turner.
Includes bibliographical references (p. 137-138) and index.
Keywords: Turner, Nat, -- 1800?-1831 -- Juvenile literature; Turner, Nat, -- 1800?-1831.; Southampton Insurrection, 1831 -- Juvenile literature; Slaves -- Virginia -- Southampton County -- Biography -- Juvenile literature; Slaves; African Americans -- Biography; Southampton Insurrection, 1831.; Southampton County (Va.) -- Biography -- Juvenile literature